rdlc 2022
DOI: 10.7764/rdlc.21.2.387
|View full text |Cite
|
Sign up to set email alerts
|

Effect of compression casting technique on the water absorption properties of concrete made using 100% recycled aggregates

Abstract: Effect of compression casting technique on the water absorption characteristics of low grade 100% Recycled Aggregate Concrete (RAC) of target strength range 11 to 15 MPa to be used in the manufacturing of masonry units is investigated. Water absorption characteristics were determined by performing sorptivity test. Recycled aggregates were produced by crushing laboratory-tested concrete samples of strength ranging from 21 MPa to 28 MPa. Two different ratios of recycled coarse aggregate and recycled fine aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Processes that include the rotor crusher or the ball mill led to reduced absorption because these techniques have a polishing effect that separates the adhered paste from the natural aggregates. Comparing the averages, it can be concluded that the jaw crusher + rotor crusher + sieving process generated FRCAs with [10,12,18,21,32,33,35,38,46,50,52,59,62] and CW [11,16,17,19,[23][24][25]36,42,43,45,47,53,57,87].…”
Section: Figure 2 Water Absorption Of Frcas From Labmentioning
confidence: 99%
See 3 more Smart Citations
“…Processes that include the rotor crusher or the ball mill led to reduced absorption because these techniques have a polishing effect that separates the adhered paste from the natural aggregates. Comparing the averages, it can be concluded that the jaw crusher + rotor crusher + sieving process generated FRCAs with [10,12,18,21,32,33,35,38,46,50,52,59,62] and CW [11,16,17,19,[23][24][25]36,42,43,45,47,53,57,87].…”
Section: Figure 2 Water Absorption Of Frcas From Labmentioning
confidence: 99%
“…The set of recycling technologies used in combination forms a recycling process. Studies show a wide variety of combinations and number of repetitions of the techniques, but in general, most include at least one crushing process and one screening process, with several studies also incorporating specific treatment technologies [39,59,82].…”
Section: Recycling Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…The issues of reducing water absorption of the construction and building materials are considered in a large number of papers [30][31][32][33][34][35][36][37][38][39][40]. To reduce water absorption of materials, various researchers suggest methods such as the use of nano-TiO2-modified recycled coarse aggregate [30], using the air entraining agent (for mortars) [31], slurry coating modified methods (for recycled coarse aggregate) [32], silane emulsion impregnation [33], cement-silica fume slurry coating method [34], compression casting method (to reduce water absorption properties of concrete) [35], impregnation with spent technical fluids [36], selective crushing [1], enrichment in heavy media [37], jigging [38], porosity enrichment on the friction classifier [39], etc. There is also a known method for reducing water absorption of liquid BFS , including pouring it with a thin layer for faster solidification [40].…”
Section: Introductionmentioning
confidence: 99%